On the identity of the name Spergularia nobreana (Caryophyllaceae) - Iamonico, Duilio; Dillenberger, Markus S. (Phytotaxa, 2023)
The name Spergularia nobreana, originally published by G. A. Sampaio from plants collected in Portugal, is investigated. A lectotype and two isolectotypes are designated on specimens preserved at PO. On the basis of a careful examination of these exsiccata, this taxon cannot be ascribed to the genus Sagina (as reported in POWO and IPNI databases where this name was considered as a synonym of Sa. hawaiensis) since it has stipules (absent in Sagina). The whole morphology of Sp. nobreana agrees with the current concept of Spergularia. The combination of characters [perennial plant, glabrous (finely glandular only in the inflorescence part); stipules triangular to lanceolate 2–3 mm long; flowers with five styles and ten stamens; sepals 4-6 mm long; capsule about 4 mm long, opening into five valves; seeds winged (wings entire or with gland-tipped papillae at the margin, brownish, less than 1/2 wide than the seeds) and unwinged] match the current concept of Sp. media s. l. Therefore, a new synonymization is proposed.